Understanding children's private speech and self- regulation learning in Web 2.0: Updates of Vygotsky through Piaget and future recommendations - Agina, A.; Tennyson, R.; Kommers, Petrus (2015)
Web 2.0 offers the Zeitgeist to update seminal research concerning children's Private Speech (PS) and Self-Regulation Learning (SRL) for application in social networks. Contemporary literature holds a body of research from the Vygotsky through Piaget to constructive theories that can be applied to theoretical foundations of Web 3.0 designs. Specifically, the purpose of the present chapter is to be present an index based on valuable and effective research concerning the subject matter in which a historical overview of both PS and SRL have demonstrated significant complexities and the most significant critiques that exist in the literature. The chapter does not mean to include detailed research methodology and results but, instead, to be used as an indexing review of PS and SRL for possible theoretical foundations in applications in the expanding world of social media. Finally, the conclusion provides a reflection on the future of our children's PS and SRL and what we should do next to enhance these concepts.